Challenges and Opportunities in Building and Maintaining a Good Therapeutic Relationship in Acute Psychiatric Settings: A Narrative Review - Bolsinger, Julia; Jaeger, Matthias; Hoff, Paul; Theodoridou, Anastasia (Frontiers in Psychiatry, 2020)
Background. The therapeutic relationship and its importance for psychotherapy outcome have been the subject of extensive research over the last decades. An acute psychiatric inpatient setting is a unique environment where severely ill patients receive intensive treatment over a limited, relatively short, period of time. This renders establishing a good therapeutic relationship difficult for various reasons. It seems likely, however, that the therapeutic relationship in such a setting plays a vital role on factors such as clinical outcome, patient satisfaction, and rehospitalization rates. Little information is available on special attributes and caveats of building and maintaining a good therapeutic relationship in an acute psychiatric setting, neither on its influence on therapy success. Methods. An extensive systematic literature search was performed using pubmed, science direct, psyc info, and google scholar databases. Keywords used were therapeutic alliance, therapeutic relationship, psychiatry, emergency, acute, coercion, autonomy, involuntary, closed ward. RCTs, observational studies, reviews, meta-analyses, and economic evaluations were included, case reports and opinion papers were excluded. Factors specific to an acute psychiatric setting were identified, and the available information was categorized and analyzed accordingly. The PRISMA statement guidelines were followed closely upon research and preparation of the present review. Results. A total of 48 studies were selected based on their relevance as well as design. They demonstrated that several factors related to setting, patient attributes, staff attributes, admission circumstances, and general situation, render building and maintaining a good therapeutic relationship difficult in an acute psychiatric setting compared to scheduled, long-term therapeutic sessions. The available literature on how to overcome this dilemma is scarce. Interventions involving staff and/ or patients have been shown to be effective in terms of relevant outcome parameters. Conclusions. Increasing research efforts, as well as raising awareness and providing specific competencies amongst clinicians and patients in terms of nurturing a good therapeutic relationship in acute settings, are necessary to improve clinical outcome, economic factors, quality of patient care and patient as well as staff satisfaction.